La regulación de los derechos de incidencia colectiva en materia ambiental en el nuevo Código Civil y Comercial de la Nación - Tolosa, Nadia Belén (2016)
The purpose of this paper is whether the incorporation of rights collective influence by the new Civil and Commercial Code is useful for more and better environmental protection. From the historical analysis we see that is not a newness. This story began in 1972 with the "Stockholm Declaration" (Declaration of the United Nations Conference on the Human Environment) and it has more than forty years, a situation which generated an overlay of special laws, local, bilateral treaties and constitutional right. We see that the protection in the latest constitutional reform were in constant collision with the principles of classic private law contained in the "Vélez code". The new code has new tools in accordance with international progress on environmental issues, such as dynamic load test, preventive action and comprehensive interpretation of the whole system (constitutionalization of private law) and incorporates the concept of sustainable consumption, of vital importance, since it represents a major factor in the production of environmental pollution. All this will certainly impact on a extension of the right to a healthy environment, and also granting stability invigorated representing the common law against special laws or interpretations court.